Zonificación funcional turística para la reactivación post terremoto del turismo en la Ciudad de Portoviejo, Manabí. - Alcívar Cabrera, Gema Leonela (2018)
The objective of this research was to design a tourist functional zoning that contributes to the reactivation of post-earthquake tourism in Portoviejo canton, Manabí province. The focus of the research was descriptive and exploratory, applying analytical and synthetic methods. The methodological procedure was structured, tending as a reference several investigative works on zoning and spatialization methods. The research was developed in four phases, resulting in: diagnosis of the tourism system in the study area; determination of legal, territorial, environmental and tourism aspects; geospatial distribution and methodological-normative guidelines for tourist functional zoning; and the establishment of strategic alliances for the tourism reactivation in Portoviejo city. This procedure allowed to establish the activities for the achievement of the specific objectives of the investigation. The results obtained proved the feasibility of the functional tourist zoning in Portoviejo city, since there are legal foundations that support a tourist organization based on the Cantonal Territorial Zoning Plan, identifying four zones: sustainable use zone; tourist area; residential area; commercial and business area. Finally, the research concluded that the design of a functional tourist zoning in Portoviejo city constitutes one of the main tools for the efficient organization of the territory, since the lack of tourist planning plans and the lack of delimitation of spaces for tourist activities, represent an important strategy for the sustainable development of tourism through the articulated management of bilateral policies between the public and private sectors that work in the locality.